Conceptions des inégalités écologiques dans cinq pays européens : quelle place dans les politiques de développement urbain durable ? - Lydie Laigle; Mélanie Tual (Développement Durable et Territoires)
This article tries to bring together information on the issue of environmental inequalities in Europe. In a first part, the history of the notion is presented insisting on the importance of socio-political cultures. An assessment of the role and place of environmental inequalities in sustainable urban development policies and public action follows this presentation. From this comparative analysis emerge the major obstacles faced by stakeholders in sustainable development regarding environmental inequalities as well as innovative ways of getting round these difficulties.